Studi Komparatif Makro Ekonomi Pemikiran Cendikiawan Muslim Klasik dan Kontemporer (Abu Ubaid, Abu Yusuf, Yahya Bin Adam, Muhammad Abdul Manan, dan M. Umer Chapra) - Muh. Ikbal; Muhtadi Ridwan; Khusnudin Khusnudin (Jurnal Ilmiah Ekonomi Islam, 2023)
The rapid development of the times makes the minds of Classical economists are increasingly being forgotten, even their books are no longer available copy it for adoption in order to realize macroeconomic science that completely in accordance with the concept of sharia. This seems comparable contrary to the thinking of contemporary economists who until now His works are still in great demand by academics The results of a comparative study of the thoughts of classical and contemporary Muslim figures have differences and similarities both in the field of monetary economics and fiscal economics. The type of research in this article is a type of research using library research. The results of a comparative study of the thoughts of classical and contemporary Muslim figures have differences and similarities in both monetary and fiscal economics. The equation about the source of state income is shadaqah, zakat and taxes. Similarities in monetary economics regarding the function of money and the prohibition of usury in financial transactions. In terms of differences in sources of income, in classical times wars often occurred so that there was a source of income for Ghanimah, namely the spoils of war.